ANTICHOLINESTERASE ACTIVITY OF OCTA PEPTIDES RELATED TO HUMAN HISTATIN 8: IN-SILICO DRUG DESIGN AND IN-VITRO - Perumal, Pandurangan; Vasudevan, Mani; Chigurupati, Sridevi; Selvaraj, Manikandan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To evaluate the octapeptides related to human histatin 8 by in-silico and in-vitro studies. Method: Schrodinger, LLC and Ellman's method. Results: The compound HH1 and HH2 was found to be potent docking score of −9.494 and −7.401 against acetylcholinesterase (AChE) enzyme. The IC50 value of HH1 and HH2 was found to be 0.39±0.28 and 0.78±0.15 μg/mL. However, these compounds are shown to be highly effective as compared with the control AChE inhibitor donepezil (0.065±0.0050 μg/mL). Conclusion: In-silico docking study was conducted for the designed octapeptides related to human histatin 8 against AChE enzyme shows significance binding affinity toward HH1 and HH2 peptides and the AChE inhibitory activity of octapeptides shown to be a highly potent inhibitor as compared with control donepezil.